Enhanced Pansharpening Using Curvelet Transform Optimized by Multi Population Based Differential Evolution - Mustafa Hüsrevoğlu,; Ahmet Emin Karkınlı, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In this study, a pansharpening process was conducted to merge the color information of low-resolution RGB images with the details of high-resolution panchromatic images to obtain higher quality images. During this process, weight optimization was performed using the Curvelet Transform method and the Multi Population Based Differential Evolution (MDE) algorithm. The proposed method was tested on Landsat ETM satellite image. For Landsat ETM data, the RGB images have a resolution of 30m, while the panchromatic images have a resolution of 15m. To evaluate the performance of the study, the proposed MDE-optimized Curvelet Transform-based pansharpening method was compared with classical IHS, Brovey, PCA, Gram-Schmidt and Simple Mean methods. The comparison process employed metrics such as RMSE, SAM, COC, RASE, QAVE, SID, and ERGAS. The results indicate that the proposed method outperforms classical methods in terms of both visual quality and numerical accuracy.
Keywords: Pansharpening; Curvelet Transform, Multi Population Based Differential Evolution; Landsat ETM; Image Processing